Comparative Capital Budgeting Practices in India: A Case Study of Selected Companies - Garg, Vipin Kumar (Journal of Commerce and Trade, 2007)
Capital budgeting is a long-term financial problem of the small as well as large industrial houses. Present study is taken to assist in project evaluation, considering- risk factor and cost of capital. The study is based on same presumptions, which have been tested, with the help of sample survey.